Talent harbour : web career portal - Sri Hartati (2014)
The recruitment function of organizations has evolved from the traditional methods of referrals, print advertisements to the use of digital platforms such as career portals. With the large amount of fresh graduates from various institutions entering the workforce every year, the recruitment function has become crucial for organizations to hire the best candidates who fit their job requirements. Likewise, jobseekers such as fresh graduates will face similar competitions in terms of securing job opportunities in their ideal organizations. With the increasing demands for interns as internships have become part of the school curriculum for most tertiary institutions, this again reflects the high level of competitions that tertiary students face in clinching their desired internships. In addition to the issue of competitive hiring market, the foreign labour quota has been a concern for many local firms and Multi-National Corporations operating in Singapore. Such quota restricts many organizations in maximizing their operations especially when they require a complex and diverse pool of human capital.